2020
DOI: 10.3390/cancers12082099
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Apoptotic Responses Elicited by Nostoc-Synthesized Silver Nanoparticles against Different Cancer Cell Lines

Abstract: Green nanoparticles represent a revolution in bionanotechnology, providing opportunities to fight life-threatening diseases, such as cancer, with less risk to the environment and to human health. Here, for the first time, we systematically investigated the anticancer activity and possible mechanism of novel silver nanoparticles (N-SNPs) synthesized by Nostoc Bahar M against the MCF-7 breast cancer cells, HCT-116 colorectal adenocarcinoma cells, and HepG2 liver cancer cells, using cell viability assays, morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 87 publications
2
37
0
Order By: Relevance
“…Moreover, most of the methods used for nanomaterial fabrication are not environmentally friendly; hence, the use of eco-friendly green approaches for the synthesis of nanoparticles was recently developed. The most developed green methods of nanoparticle fabrication using plant extracts, fungi, algae, and bacteria were reviewed recently by El-Seedi et al ( 2019 ) and Hamida et al ( 2020 ). Several metal nanoparticles were successfully synthesized using these approaches including silver nanoparticles (Bin-Meferij and Hamida 2019 ) and ZnO-NPs (Lakshmi et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the methods used for nanomaterial fabrication are not environmentally friendly; hence, the use of eco-friendly green approaches for the synthesis of nanoparticles was recently developed. The most developed green methods of nanoparticle fabrication using plant extracts, fungi, algae, and bacteria were reviewed recently by El-Seedi et al ( 2019 ) and Hamida et al ( 2020 ). Several metal nanoparticles were successfully synthesized using these approaches including silver nanoparticles (Bin-Meferij and Hamida 2019 ) and ZnO-NPs (Lakshmi et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the biosynthesis of NPs via microbial synthesis has many drawbacks, which may include achieving a homogenous shape, symmetry, composition and size of NPs which is governed by environmental conditions, such as temperature and pH of the medium [ 71 ]. Although recent studies have shown the huge potential of microbes for the synthesis of novel NPs and their use in biomedicines and cancer treatment [ 257 , 258 , 259 ], the methods of biosynthesis using microbes need to be modified for commercial production, and the synthesis of NPs needs to be scaled up compared to traditional methods. Moreover, an in-depth investigation is required to study the toxicity, biocompatibility and potential effect of NPs on the immune system, respiratory system, hepatobiliary system, reproductive system, kidney, eyes, skin and other organs [ 260 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…[ 4 , 147 ]. The most frequently studied MNPs are Ag-NPs and Au-NPs due to their significant therapeutic activity against many serious diseases and their smaller-size-to-large-surface-area ratio, which enables them to be used as drug delivery systems and catalysts [ 8 , 148 ].…”
Section: Lichens As Biosynthesizers For Nanoparticlesmentioning
confidence: 99%